Stable isotopes to study sulfur amino acid utilization in broilers - Suzuki, R. M. [UNESP] (2020)
Nutritionists have been discussing whether the dietary supplementation of cyst(e)ine is required as a part of the dietarymethionine (Met)in thetotal sulfur amino acid (TSAA)requirement to achieve optimum performance in broilers. Part of Met is converted tocysteine (Cys)to meet the Cys requirement, especially for feather growth. The TSAA requirement has been determined by using graded levels of free Met in the diet, without supplementation of free cyst(e)ine. It has also been argued that the Met to Cys ratio (Met:Cys) changes with age and even with different Met sources. The objective of this study was to evaluate the two sources of Met, while determining the proportion of Met and Cys in total dietary TSAA that optimize the performance of broilers. A performance assay was carried out in a factorial arrangement (5 x 2) using 1080 broilers from 42 to 56 days of age fed diets having different dietary proportions of Met and Cys (44 : 56, 46 : 54, 48 : 52, 50 : 50 or 52 : 48) while maintaining the same dietary TSAA in the diets. Two synthetic Met sources (dl-Met orl-Met) were used for each of the diets with different dietary Met : Cys ratios. Twenty-one broilers of the same age were fed the diets 44 : 56, 48 : 52 and 52 : 48 by supplementing the diet with L-(N-15) Met or L-(N-15(2)) Cystine to study the metabolism of TSAA. No differences were observed between Met sources for feed intake, BW gain and feed conversion ratio (FCR;P> 0.05); however, FCR was numerically improved at 50 : 50 Met : Cys. Regarding TSAA utilization, the conversion of Met to Cys increased with increase in Met : Cys ratios, but the concentration of Met intermediates decreased. Broiler chickens responded to different dietary proportions of sulfur amino acids by altering their sulfur amino acid metabolism, and diets containing 50 : 50 Met : Cys is recommended for broilers of age 42 to 56 days.